THE ROLE OF CORPORATE PUBLIC RELATIONS IN BUILDING BRAND VOICE AT PTPN IV REGIONAL I MEDAN - Ryan Dwi Cahya; Indira Fatra Deni Peranginangin (Program Pascasarjana UIN Sumatera Utara, 2026)
The development of digital media encourages companies, including State-Owned Enterprises (SOEs), to build strategic and consistent corporate communications through social media to strengthen the company's identity and reputation. This study aims to analyze the role of Corporate Public Relations of PTPN IV Regional I Medan in building the company's brand voice through the Instagram account @n4r1_mediacorporate. The study uses a qualitative approach with descriptive methods to understand the corporate communication practices carried out by public relations in translating the company's identity into digital communications. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies, while data analysis was carried out through data reduction, data presentation, and drawing conclusions using source triangulation techniques to ensure data validity. The results of the study indicate that Corporate Public Relations of PTPN IV Regional I Medan has a strategic role in building the company's brand voice through consistent, communicative, persuasive, educational, and informative digital communications with a semi-formal communication style adapted to the characteristics of social media without eliminating the company's professional identity as a SOE. Digital communication management through Instagram is considered quite effective in increasing audience engagement through interactions in the form of comments, likes, and positive responses to company content, and is able to strengthen the company's image and relationship with the public. However, this study also identified several challenges in maintaining brand voice consistency, such as rapidly changing social media trends, differences in creative ideas within the team, and adapting communication styles to diverse audiences. Therefore, increasing content creativity, posting consistency, and developing more interactive communication strategies is necessary to strengthen a company's brand voice and make it more relevant in the digital age.